Kepastian Hukum Pencipta dan Pemegang Hak Cipta Gojek-PT Aplikasi Karya Anak Bangsa (Studi Kasus Perkara Nomor 86/Pdt.Sus-HKI/Cipta/2021/PN Niaga Jkt.Pst) - Asma Karim (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
ABSTRACT This study aims to determine and analyze how the legal certainty about who is actually the creator and copyright holder of Gojek-PT application of the work as well as how the consideration should be taken by the judge in examining and deciding the case based on the provisions of Law No. 28 of 2014 on copyright (copyright law). The research method used in this study is normative juridical law research based on secondary data or literature studies. The results showed: first: legal certainty about who is actually the creator and copyright holder of the Gojek-PT aplikasi Karya Anak Bangsa is in a lawsuit with Case Number 86/Pdt.Sus-HKI / copyright / 2021 / PN Niaga Jkt.Pst, a copyright lawsuit can be filed if the software used by gojek is proven to be legally and convincingly an imitation or imitation of a similar product owned by the plaintiff. As long as it has not become a fixation or is realized in a tangible form, such as source code, Gojek can link its software. The legal certainty is that the plaintiff remains the owner of the online motorcycle taxi, and the defendant is also the creator and copyright holder of the Gojek-PT Karya Anak Bangsa application. Second: the consideration taken by the judge in examining and deciding the case based on the provisions of the Copyright Law is in the process of proving the plaintiff and defendant. If no legal facts are found that can indicate that the defendant committed copyright infringement, the plaintiff's lawsuit is considered vague, unclear / obscure libel. The plaintiff will also be declared as a party that has no legal standing or an interested party to file a quo lawsuit (Article 97 paragraph (1) of the Copyright Law). Keywords: Legal Certainty, Legal Protection, Creator, Copyright Holder, Gojek